Clinical pharmacology principles for analgesics in neonates and infants - Allegaert, Karel (Henry Stewart Talks, 2024)
Neonatal and infant physiology, Developmental pharmacokinetics and pharmacodynamics, Distribution volume, Clearance of Developmental pharmacokinetics, Phase I and phase II metabolism, Covariates of drug metabolism, Pediatric formularies